Status of soil, fodder and serum (cattle) mineral in high rainfall area of NE region - DAS, GUNJAN; SHARMA, M C; JOSHI, CHINMAY; TIWARI, RUPASI (The Indian Journal of Animal Sciences, 2011)
A study was conducted to record the mineral status in soil, fodder and serum from 4 districts of Tripura state, viz. West, South, North and Dhalai Tripura. Soil samples from these districts showed an overall average prevalence of phosphorus, zinc, copper and cobalt deficiency. Similarly, overall prevalence of calcium (Ca), magnesium (Mg), phosphorus (P), zinc (Zn), copper (Cu), iron (Fe), cobalt (Co), and selenium (Se) deficiency in fodder was 8.24%, 9.61%, 27.47%, 44.78%, 30.21%, 4.12%, 39.28%, and 4.67% respectively. The overall prevalence of serum P, Zn, Cu, Co, and Se deficiency was 30.03%, 36.75%, 35.96%, 38.73% and 6.32% respectively. Cattle of Tripura State were highly deficient in phosphorus. Soil, fodder and cattle of Tripura State were highly deficient in zinc followed by copper and cobalt.